Combination Susceptibility Testing of Common Antimicrobials in Vitro and the Effects of Sub-MIC of Antimicrobials on Staphylococcus aureus Biofilm Formation - Yang, Bing; Lei, Zhixin; Zhao, Yishuang; Ahmed, Saeed; Wang, Chunqun; Zhang, Shishuo; Fu, Shulin; Cao, Jiyue; Qiu, Yinsheng (Frontiers in Microbiology, 2017)
The current study was conducted to evaluate the antibacterial combination efficacies, and whether the sub-inhibitory concentrations (sub-MIC) of antibiotics can influent on the biofilm formation of S. aureus. The minimum inhibitory concentration (MIC) of common antibacterial drugs was determined in vitro against clinical isolates of Staphylococcus aureus, Escherichia coli and Pasteurella multocida alone and in combination with each other by using the broth microdilution method and the checkerboard micro-dilution method analyzed with the fractional inhibitory concentration index (FICI), respectively. Regarding these results, antibacterial drug combinations were categorized as synergistic, interacting, antagonistic and indifferent, and most of the results were consistent with the previous reports. Additionally, the effects of sub-MIC of seven antimicrobials (kanamycin, Acetylisovaleryltylosin tartrate, enrofloxacin, lincomycin, colistin sulfate, berberine, and clarithromycin) on S. aureus biofilm formation were determined via crystal violet staining, scanning electron microscopy (SEM) and real-time PCR. Our results demonstrate that all antibiotics, except Acetylisovaleryltylosin tartrate, effectively reduced the S. aureus biofilm formation. In addition, real-time reverse transcriptase PCR was used to analyze the relative expression levels of S. aureus biofilm-related genes such as sarA, fnbA, rbf, lrgA, cidA and eno after the treatment at sub-MIC with all of the six antimicrobials. All antibiotics significantly inhibited the expression of these biofilm-related genes except for acetylisovaleryltylosin tartrate, which efficiently up-regulated these transcripts. These results provide the theoretical parameters for the selection of effective antimicrobial combinations in clinical therapy and demonstrate how to correctly use antibiotics at sub-MIC as preventive drugs.